A case of recurrent spontaneous pneumothorax during pregnancy treated with video assisted thoracoscopic surgery. (13th August 2012) - Nwaejike, Nnamdi; Aldam, Poppy; Pulimood, Thomas; Giles, Roger; Brockelsby, Jeremy; Fuld, Jonathan; Hughes, jacqueline; Coonar, Aman
Abstract : Pneumothorax during pregnancy is uncommon. Recently ambulatory chest drainage has been advised to treat the pneumothorax and to cover the delivery period. This imposes restrictions on the mother with associated co-morbidity. The authors present a case of recurrent chest-tube resistant pneumothorax during pregnancy which had persisted for 4-weeks. To guide management of a patient referred in the third trimester of pregnancy the authors undertook a systematic review. This led to definitive video assisted thoracoscopic surgery (VATS) for bullectomy and pleurodesis which was successful without either peri-operative or peri-partum complications or recurrence of pneumothorax. Our review suggests that a VATS approach during pregnancy is both safe and effective.